2020
DOI: 10.1186/s13089-020-00167-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to learning and using point-of-care ultrasound: a survey of practicing internists in six North American institutions

Abstract: Background: Point-of-care ultrasound (POCUS) is increasingly used in internal medicine, but a lack of trained faculty continues to limit the spread of POCUS education. Using a framework based on organizational change theories, this study sought to identify barriers and enablers for hospital-based practicing internists to learn and use POCUS in clinical practice. Methods: We invited practicing internists at six North American institutions to participate in an electronic survey on their opinions regarding 39 bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 25 publications
5
79
0
Order By: Relevance
“…Unfortunately, our data revealed that opportunities to perform procedures were missed because supervisors were not available. This observation is consistent with previous data highlighting that few general internists are able to teach procedural skills [ 29 ] and that many programmes lack trained faculty [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Unfortunately, our data revealed that opportunities to perform procedures were missed because supervisors were not available. This observation is consistent with previous data highlighting that few general internists are able to teach procedural skills [ 29 ] and that many programmes lack trained faculty [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Institutional support for faculty training and the infrastructure for ongoing quality assurance processes with a secure system for archiving images must be prioritized [ 30 ]. This will require the support of the radiology department and fully certified interventional radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, faculty expertise is critical for effective integration of POCUS into GME. 25,34,35 Residency leadership interested in developing competency-based POCUS curricula must consider investing in the development of POCUS expertise in their clinical educators as a foundational strategy.…”
Section: Trainingmentioning
confidence: 99%
“…This phenomenon of using ultrasound without training is true not only of learners in Saudi Arabia. In a multi-center survey of practicing internists in North America, the number of practitioners who reported using ultrasound exceeded those who reported prior training [ 10 ].…”
mentioning
confidence: 99%
“…In addition, to provide quality control and maintain standards, infrastructure support with a secure imaging archiving system is also needed. One key barrier encountered in many programs is the lack of trained faculty [ 10 ]. Thus, providing institutional support for faculty to be trained and infrastructure for ongoing quality assurance processes should be a priority [ 10 ].…”
mentioning
confidence: 99%